Purchasing Power Parity in Transition Economies Application for the Czech Republic - Dúbravská, Pavla; Taušer, Josef; Klosová, Anna, 1942-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2007)
The goal of this diploma thesis is to assess purchasing power parity (PPP) under the conditions of transition process. The thesis provides a survey of the purchasing power parity theory and concentrates on the relative version. It outlines main causes of possible deviations and modifications of the model. In the empirical part four transition economies are tested for the PPP theory: the Czech Republic, Hungary, Poland and Slovakia. The diploma thesis concludes with analysis of the role of the exchange rate under conditions of a small open economy. The overall analysis is implemented within the context of real and nominal convergence towards European Union and future accession to the European Monetary Union
Vedoucí práce: Josef Taušer
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2007
Rok obhajoby 2007
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses